2000
DOI: 10.1080/003655900750016904
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of Prostate Cancer Patients by On-demand Contacts with a Specialist Nurse: A Randomized Study

Abstract: Our study indicates that men with prostate cancer can be safely followed up by a specialist nurse. The study results show that this alternative follow-up is cost-effective, especially in men without metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 15 publications
1
93
0
4
Order By: Relevance
“…Few studies so far have considered costs of followup specifically [3,4,21,23], and, in two recent reviews [24,25], it remains unclear what specific values and to what extent follow-up procedures are included in the total cost. As stated by Sikora and Bosanquet [25] more information is needed on how to use staff time most effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies so far have considered costs of followup specifically [3,4,21,23], and, in two recent reviews [24,25], it remains unclear what specific values and to what extent follow-up procedures are included in the total cost. As stated by Sikora and Bosanquet [25] more information is needed on how to use staff time most effectively.…”
Section: Discussionmentioning
confidence: 99%
“…More recent randomized controlled trials of specialized oncology nurse-led care have demonstrated similar results for patients with advanced lung cancer, breast cancer, and prostate cancer (Bredin et al, 1999;Corner, Plant, A'Hern, & Baile, 1996;Faithfull, Corner, Meyer, Huddart, & Dearnaley, 2001;Hegelson et al, 2000;Loftus & Weston, 2001;Ritz et al, 2000). Patients, randomized to specialized oncology nurse-led care, demonstrated improved satisfaction with care, better quality of life, decreased symptoms of anxiety and depression, improvements in performance status even in the context of progressive disease, decreased symptom distress, and up to a 37% reduction in health care costs compared to patients receiving standard care alone.…”
Section: Research Supports the Standards Of Carementioning
confidence: 72%
“…Grunfeld et al [6] found that patients with breast cancer were more satisfied with follow-up in general practice than they were with that received in hospital outpatient departments. Similarly, the outcomes of Anderson et al [7] demonstrated that specialist nurses could effectively follow-up patients with prostate cancer and that this was cost-effective, especially in those without metastatic disease.…”
Section: Discussionmentioning
confidence: 99%